High-efficiency solar thermoelectric conversion enabled by movable charging of molten salts - Chang, Chao; Wang, Zongyu; Fu, Benwei; Ji, Yulong (Scientific reports, 2020)
Solar energy as an abundant renewable resource has been investigated for many years. Solar thermoelectric conversion technology, which converts solar energy into thermal energy and then into electricity, has been developed and implemented in many important fields. The operation of solar–thermal–electric conversion systems, however, is strongly affected by the intermittency of solar radiation, which requires installation of thermal storage subsystems. In this work, we demonstrated a new solar–thermal–electric conversion system that consists of a thermoelectric converter and a rapidly charging thermal storage subsystem. A magnetic-responsive solar–thermal mesh was used as the movable charging source to convert incident concentrated sunlight into high-temperature heat, which can induce solid-to-liquid phase transition of molten salts. Driven by the external magnetic field, the solar–thermal mesh can move together with the receding solid–liquid interface thus rapidly storing the harvested solar–thermal energy within the molten salts. By connecting with a thermoelectric generator, the harvested solar–thermal energy can be further converted into electricity with a solar–thermal–electric energy conversion efficiency up to 2.56%, and the converted electrical energy can simultaneously light up more than 40 orange-colored LEDs. In addition to stable operation under sunlight, the charged thermal storage subsystem can release the stored heat and thus enables the solar–thermal–electric system to continuously generate electricity after removal of solar illumination.